(untitled) (Fiep Bulletin - online, 2014)
Until a few years ago, the role of the nurse in the operating room was related to managerial aspects, the impersonal conduct of professionals working in the operating room, which may be due to the high demand for services and constant contact with people under stress, but, at times, the inadequate medical care and the lack of professionals left the patient, in such circumstances, exposed to the loss of identity and lack of privacy. This paper points out, as the objective, the main articles related to humanization of the operating room, identifying key needs and highlighting the importance of humanizing nursing care in patients under surgery. This study consists of a systematic literature search, with qualitative approach, in which a literature review in scientific journals was conducted, focusing on articles from the SciELO database, considering the content published between the years 2006 and 2012. 18 (eighteen) articles related to the topic were found after having performed the search in the database mentioned above, discarding 6 (six), since they did not fulfil the agreed inclusion criteria. Then, twelve (12) articles were used, subjected to analysis. According to the studied literature, it was observed that nursing care and technology are linked, and the professional gets engaged in theories and principles that result in the expression of technical and scientific knowledge. Daily situations and relationships experienced by nurses in operating rooms trigger sensations of pleasure and pain. When facing conflict situations, the nurse should minimize them, talk to the patient, in a participative way, itinerant. Ethical actions, contemplated in the graduation course, should be practiced by nurses when assisting their patients. However, the repetition of daily activities induces the professional to act mechanically. Work overload and even the indulgence affect considerably the relationship practice/theory, showing indications of customer dissatisfaction regarding the care received.